Design of Automatic Gate Rolling Door Control System Using Rain Drop Sensor - Taufiqurrohman, Afan; Simanjuntak, Imelda (Program Studi Teknik Elektro Universitas Khairun, 2023)
Rolling doors used by small-scale industrial companies are still operated manually with conventional up, down, and stop button panels. This is the cause of the problem of inefficient transportation mobility that operates and causes product losses due to rainwater splashing that enters the warehouse. Therefore, this study aims to implement an automatic rolling door with a DC motor drive assisted by a raindrop sensor. The research method used is a literature study approach: identifying problems, determining the focus and research objectives, designing and implementing prototype solutions, testing, discussing, and drawing conclusions. Based on system testing, it was found that the response time for reading the rain sensor took 1.19 seconds, and the response time for reading the rain sensor to detect light again was 0.92 seconds. The delay time for the DC motor to rotate to close the gate when it receives a sensor signal in rainy conditions is 1.34 seconds, and the delay time for opening the gate when it receives a sensor signal that is bright again or the sensor is dry is 0.98 seconds. Based on the results of system testing, it was found that the delay time buzzer sounded as a warning sign if someone crossed it for 0.86 seconds. Overall, the test results show that the system is running well according to the functions, and system algorithms are active at the same time.